Factors Influencing the Purchase Decisions of The Engineering Instruments by Food and Beverage Manufacturing Companies in Bangkok and Its Vicinity: Factors Influencing the Purchase Decisions of The Engineering Instruments by Food and Beverage Manufacturing Companies in Bangkok and Its Vicinity - Kaewmanee, Tawatchai; Keawkasetkon , Phinit (RATANABUTH JOURNAL, 2025)
Executives and engineers at the supervisory level make decisions about purchasing measuring equipment based on 5 factors: awareness of needs; Seeking information Evaluation of alternatives purchasing decision and post-purchase behavior. This is especially important in the decision to purchase measuring equipment by executives and engineers at the supervisory level, directly affecting the efficiency of quality control. and ability to compete in the market Companies that choose to use measuring instruments that are inappropriate or of insufficient quality may encounter problems in quality control. This may adversely affect consumer confidence and the ability to conduct business. This research objectives are to 1) study personal factors that affect the decision to purchase engineering measuring instruments of food and beverage manufacturing companies. in Bangkok and surrounding areas. 2) Study the 5A's marketing strategies that affect the decision to purchase engineering measuring equipment of food and beverage production companies in Bangkok and surrounding areas. It is quantitative research. The sample group is 385 executives or representatives in the food and beverage industry who are responsible for making decisions about purchasing engineering measuring instruments. The research instrument used is a questionnaire with a reliability value of .917. Statistics used in data analysis include percentage, mean, and standard deviation. By One-way ANOVA and Multiple Regression Analysis. The results of the study found that (1) Comparing the decision to purchase engineering measurement tools of food and beverage manufacturing companies is different when classified according to personal factors, namely educational level and work experience. The differences are statistically significant at the .01 level.(2)strategies 5A's marketing that affect the decision to purchase engineering measurement tools of food and beverage production companies in Bangkok and surrounding areas, overall, 51.6 percent (Adjusted R2 = .516) It was found that the 5A's marketing strategy factors, namely interest (P-value=.001, Beta=.215), inquiry (P-value=.001, Beta=.203), decision (P-value=.001, Beta=.171), word of mouth (P-value=.001, Beta=.288), have a positive influence on the decision to purchase engineering measuring instruments of food and beverage manufacturing companies with statistical significance at the .01 level. (3) Executives and supervisory engineers should study the decision to purchase engineering measurement tools from food and beverage manufacturing companies. This will help enhance understanding of the purchasing decision process and lead to effective tool selection.